A method for preparing a long-lived nano-ion probe aperture

By using long-lived apertures prepared with tungsten material, micropores are formed by using electric spark and femtosecond laser processing and low-temperature tempering, the irreversible loss problem caused by high-energy primary ion beam bombardment is solved, which significantly extends the service life and improves the stability and analysis accuracy of the nanoion probe.

CN119566747BActive Publication Date: 2025-05-02INSTITUTE OF GEOLOGY AND GEOPHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510138208.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-05-02
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

The nanoion probe aperture is irreversible due to high-energy primary ion beam bombardment, which affects the stability and analysis accuracy of the instrument.

Method used

A long-life diaphragm is prepared using tungsten material, and micropores are formed by electric spark drilling and femtosecond laser processing, and low-temperature tempering is carried out to cure the metal structure around the aperture diameter and improve the strength and stability of the micropores.

Benefits of technology

It significantly extends the service life of the aperture, improves the stability and analysis accuracy of nano-ion probes, and reduces equipment maintenance costs and replacement frequency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119566747B_ABST
    Figure CN119566747B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a long-life nano-ion probe aperture, comprising the following steps: 1) preparing an aperture metal sheet; 2) obtaining a conical pit structure on the surface of the aperture metal sheet by an electric spark drilling method; 3) machining a microhole in the center of the conical pit by a femtosecond laser, and obtaining the aperture by wire cutting the outer diameter of the aperture; 4) tempering the aperture; 5) testing the loss of the aperture by a nano-ion probe. The aperture has the advantages of high stability, low loss, and long service life. Compared with existing aperture products, its service life is extended by 30 times, and it is suitable for use with a nano-ion probe, providing a basis for the stability of a nano-ion probe instrument.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of universal components for mass spectrometry and scanning electron microscope, and in particular relates to a method for extending the service life of a long-life nano-ion probe aperture. Background Art

[0002] NanoSIMS is a secondary ion probe mass spectrometer that uses a primary ion beam to bombard solid samples to generate secondary ions for mass spectrometry analysis. Compared with other ion probe instruments, NanoSIMS has the advantage of extremely high spatial resolution, with a maximum resolution of up to 50nm, and can perform elemental content and isotope composition analysis on the micron-submicron scale of solid samples.

[0003] The spatial resolution of the nano-ion probe mainly depends on the design and deployment of the primary ion transmission optical path. In the optical system of primary ions, the aperture is a part that directly limits the energy and beam spot size of the primary ion beam. It is a small disc with an outer diameter of 2mm and a thickness of 0.6mm. There are molybdenum, platinum and gold aperture products on the market. Among them, molybdenum apertures are commonly used for nano-ion probes because of their good durability. The aperture is installed below the exit of the ion source, and apertures with apertures of 50μm and 100μm are commonly used; the smaller the aperture of the aperture, the smaller the beam spot size of the primary ion, and the higher the spatial resolution of the instrument. However, due to the high energy and temperature of the oxygen ion source, the aperture will cause serious loss, and its aperture size and shape will be destroyed, resulting in the energy of the primary ion not being properly limited, causing changes in the test signal and spatial resolution during the analysis process.

[0004] Aperture loss is an irreversible phenomenon and needs to be solved by replacing the new aperture diaphragm. First, the primary optical path of the air-breaking instrument needs to be replaced, and then the vacuum is re-drawn and the equipment is debugged. This process not only takes a long time to adjust the instrument status, but also there are certain risks in the maintenance process, which is not conducive to maintaining a stable state of the nano-ion probe instrument.

[0005] In view of the problem that the existing aperture is easy to wear out, the present invention provides a method for developing a long-life aperture. Compared with the existing aperture products, the service life of the aperture is extended by 30 times, and it is suitable for use in nano-ion probes, providing a basis for the stability of nano-ion probe instruments. Summary of the invention

[0006] In order to solve the technical problem of irreversible loss of the aperture due to energy bombardment, which leads to poor stability of the nano-ion probe, the present invention optimizes the material and aperture structure of the aperture, selects a suitable processing method, and verifies the effect of the aperture through reasonable verification methods, thereby obtaining a long-life aperture material that can be widely used in ion probe processes.

[0007] In a first aspect, the present invention provides a method for preparing a long-lived nano-ion probe aperture, comprising the following steps:

[0008] The first step is to prepare the aperture metal sheet.

[0009] Furthermore, the aperture material is selected from molybdenum, tungsten, platinum or gold, preferably tungsten.

[0010] The aperture metal sheet has a thickness of 0.58-0.60 mm, a length of 20-30 mm, a width of 20-30 mm, and a roughness Ra<0.1.

[0011] Since the aperture is installed directly below the ion source, it is directly bombarded by the high-energy primary ion beam during use. Due to the effects of high temperature and mechanical impact, the aperture of the aperture increases and is damaged, resulting in unstable changes in the test signal and spatial resolution during the analysis process. The non-precious metal molybdenum aperture is the most durable of the existing products, so the material selection focuses on metal materials with a higher melting point and hardness than molybdenum. Tungsten has a high melting point, high hardness, good thermal conductivity and excellent antioxidant ability, making it the preferred material for the present invention.

[0012] In the second step, a conical pit structure is obtained on the surface of the aperture metal sheet by using an electric spark drilling method.

[0013] Furthermore, the depth of the conical pit structure is 0.45-0.60 mm, and the cone angle is 85-95°.

[0014] Furthermore, the conditions of the electric spark are peak current 8-12A, gap voltage 80-200V, pulse interval 1-100μs, and pulse width 1-100μs.

[0015] In the third step, a femtosecond laser is used to process a microhole in the center of the conical pit, and the outer diameter of the diaphragm is cut by wire cutting to obtain the diaphragm.

[0016] Furthermore, the conditions of the femtosecond laser are: wavelength 1000~1100nm, power 5~20W, repetition rate 1Hz~1MHz, pulse width 190fs~10ps, and maximum pulse energy 10~100μJ.

[0017] Furthermore, the micropore diameter is 50-100 μm, and the accuracy is ±5 μm.

[0018] Furthermore, the wire cutting uses a diamond wire with a wire diameter of 0.35 mm, water or cutting oil as a coolant, and sets the cutting speed to 0.2 m / s for cutting.

[0019] Furthermore, the aperture is a disc with an outer diameter of 1.98-2.02 mm.

[0020] The fourth step is to temper the aperture.

[0021] Furthermore, the tempering treatment is carried out in an inert atmosphere at a temperature of 450-500° C. for 1-2 hours and then naturally cooled to room temperature.

[0022] Preferably, the temperature rising conditions during the tempering process are:

[0023] When the temperature is lower than 200°C (i.e., room temperature ≤ temperature < 200°C), the heating rate is 5~6°C / min;

[0024] When the temperature is between 200°C (inclusive) and 500°C (ie, 200°C ≤ temperature ≤ 500°C), the heating rate is 1~2°C / min.

[0025] The present invention controls the heating conditions in different temperature zones so that the crystal structure of the metal sheet is arranged more regularly during the tempering process, which is beneficial to the stability of the metal lattice structure and the optimization of the metal organization structure, thereby solidifying the metal structure around the aperture, improving the strength of the micropores, and reducing the probability of aperture loss.

[0026] Optionally, after the diaphragm is tempered, the quality specifications of the diaphragm need to be checked, including checking parameters such as the diaphragm thickness, outer diameter, micro-hole diameter, centering, and roundness.

[0027] Optionally, the method further includes ultrasonically cleaning and drying the diaphragm.

[0028] The fifth step is to use a nano-ion probe to test the loss of the aperture.

[0029] The prepared aperture is installed in the nano-ion probe device to monitor and observe the change in the energy of the primary ion beam after passing through the aperture. The increase in beam energy indicates that the aperture has been lost.

[0030] The ion beam energy change uses the Beam Stability function in the Tunning software to record the change of the primary ion beam current intensity, and calculate and compare the primary ion beam energy change rate. Specifically, the relative change rate of the primary ion beam energy value recorded at different time points to the initial value is calculated.

[0031] In this field, metals are generally processed by laser. However, the aperture of the diaphragm to be processed is small, the thickness is large, and the roundness and centering requirements are high; in addition, the metal (such as tungsten) has a high melting point and high hardness, which makes processing difficult. In addition, laser processing of microholes causes microcracks in the hole wall and debris accumulation, which reduces the strength of the aperture of the diaphragm and affects its service life. The present invention uses the electrospark processing method of inverted cone microholes to process a conical pit with a depth of 0.45~0.60mm and a cone angle of about 90° on the surface of a flat metal sheet, and then uses a femtosecond laser to process a microhole in the center of the conical pit. Finally, the outer diameter of the diaphragm is processed by wire cutting, which can improve the accuracy and stability of the diaphragm processing, so that the diaphragm processing error is small, the precision is high, and it is more in line with the use requirements. Finally, the processed aperture is subjected to low-temperature annealing treatment to solidify the metal structure around the aperture and improve the strength and stability of the micropores, thereby obtaining a long-life aperture material, which greatly increases the service life of the aperture. This not only reduces equipment costs and simplifies the process of replacing consumables, but also improves the accuracy and stability of test signals and test results during nano-ion probe testing.

[0032] In a second aspect, the aperture prepared according to the first aspect of the present invention is used in nano-ion probe detection and analysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Schematic diagram of the aperture structure of the present invention, wherein 1-outer diameter; 2-thickness; 3-cone angle; 4-microhole diameter; 5-cone pit depth;

[0034] Figure 2 The beam usage of the aperture in Example 1 (aperture 100 μm);

[0035] Figure 3 The beam usage of the existing molybdenum aperture product with an aperture of 100μm;

[0036] Figure 4 The beam usage of the aperture in Example 2 (aperture 50 μm);

[0037] Figure 5 The beam usage of the existing molybdenum aperture product with an aperture of 50μm;

[0038] Figure 6 The aperture change of Example 2 (aperture 50 μm) before and after the aperture test;

[0039] Figure 7 The beam usage of the aperture in comparative example 1 (aperture 50 μm);

[0040] Figure 8 The aperture change of comparative example 1 (aperture 50 μm) before and after the aperture test. DETAILED DESCRIPTION

[0041] Example 1 (Tungsten aperture with an aperture of 100 μm)

[0042] The first step is to prepare the aperture metal sheet: prepare a tungsten sheet with a thickness of 0.6mm and a length and width of 30mm. Check the parallelism and roughness of the upper and lower planes of the tungsten sheet to ensure that the surface roughness Ra of the tungsten sheet does not exceed 0.1.

[0043] In the second step, a conical pit with a depth of 0.50±0.02 mm and a cone angle of 90° is machined on the flat tungsten sheet by using an electrospark process, wherein the electrospark process adopts the parameter settings of a peak current of 12A, a gap voltage of 100V, a pulse interval of 80μs, and a pulse width of 80μs.

[0044] The third step is to use a femtosecond laser to process a small hole (or microhole) with a diameter of 100μm in the center of the above-mentioned inverted cone hole, with an error of no more than 5μm. With the above-mentioned small hole as the center, a circular slice with an outer diameter of 2 +0 / -0.02 mm is processed by wire cutting to obtain an aperture. The femtosecond laser processing adopts the parameter settings of wavelength 1028nm, average power 10W, repetition rate 1000Hz, pulse width 270fs, and maximum pulse energy 80μJ.

[0045] The fourth step is to perform segmented tempering on the aperture obtained in the previous step. When the temperature is below 200°C, the heating rate is 5°C / min; after the temperature reaches 200°C, the heating rate is changed to 1°C / min until the temperature reaches 500°C, and then kept at this temperature for 1 hour, and then naturally cooled to room temperature. All operations are carried out under nitrogen protection.

[0046] After the process is completed, the quality specifications of the aperture are checked: the thickness of the aperture obtained by the above process is 0.596 mm, the outer diameter is 1.990 mm, the diameter of the small hole is 98 μm, the center degree is 0.02 mm, and the roundness is ≤ 1 μm, which meets the processing requirements. Then, the aperture that meets the requirements is ultrasonically cleaned and dried.

[0047] The fifth step is to test the loss of the aperture using a nano-ion probe: install the tungsten aperture onto the diaphragm plate D0 of the nano-ion probe instrument, adjust the physical position of the aperture and the focusing position of the primary beam, and allow the primary ion beam to pass through the center of the aperture. Use the Beam Stability function in the Tunning software that comes with the nano-ion probe to record the change in the primary ion beam intensity; the cumulative recording time is 40 hours, and the recording interval is 5 minutes; compare the relative change rate of the primary ion beam intensity value at different time points with the initial value. The rate of change of the primary ion beam intensity can reflect the stability of the aperture. The present invention monitors the rate of change of the primary ion beam energy through the commercial aperture, the embodiment and the comparative aperture samples, and records the time when the rate of change does not exceed 1% as the service life of the aperture. The results are shown in Table 1.

[0048] Table 1 Service life of different apertures

[0049] .

[0050] The beam usage results of the aperture in Example 1 are shown as follows ( Figure 2 As shown in Table 1, the energy of the primary ion beam is stable within the first 32 hours; after 32 hours, the beam energy increases slowly, which means that the aperture is worn out. This shows that the aperture prepared by the preparation method of the present invention can maintain a stable beam for 32 hours. The commercially available aperture (aperture of 100 μm) has the same beam usage conditions (such as Figure 3 As shown in the figure, the beam stabilization time is only 0.9 hours, which shows that compared with the current commercial products with the same aperture, the service life of the aperture prepared in Example 1 of the present invention is increased by 35 times, which has obvious technical advantages over the existing products. The long-life aperture is of great significance to the application of the product and the stability of the detection process.

[0051] Example 2 (Tungsten aperture with an aperture of 50 μm)

[0052] The first step is to prepare the aperture metal sheet: prepare a tungsten sheet with a thickness of 0.6 mm and a length and width of 10 mm. Check the parallelism and roughness of the upper and lower surfaces of the tungsten sheet to ensure that the roughness Ra does not exceed 0.1.

[0053] In the second step, a conical pit with a depth of 0.25±0.02 mm and a cone angle of 90° is machined on the flat tungsten sheet by using an electrospark process with a peak current of 12A, a gap voltage of 100V, a pulse interval of 80μs, and a pulse width of 80μs.

[0054] The third step is to use a femtosecond laser to process a small hole (or microhole) with a diameter of 50μm in the center of the above-mentioned inverted cone hole, with an error of no more than 5μm. With the above-mentioned small hole as the center, a circular slice with an outer diameter of 2 +0 / -0.02 mm is processed by wire cutting to obtain an aperture. The femtosecond laser processing parameters are: wavelength 1028nm, average power 10W, repetition rate 1000Hz, pulse width 270fs, and maximum pulse energy 80μJ.

[0055] The fourth step is to perform segmented tempering on the aperture obtained in the previous step. When the temperature is below 200°C, the heating rate is 5°C / min; after the temperature reaches 200°C, the heating rate is changed to 1°C / min until the temperature reaches 500°C, and then kept at this temperature for 1 hour, and then naturally cooled to room temperature. All operations are carried out under nitrogen protection.

[0056] After the process is completed, the quality specifications of the aperture are checked: the thickness of the aperture obtained by the above process is 0.589 mm, the outer diameter is 1.997 mm, the diameter of the small hole is 51 μm, the center is 0.02 mm, and the roundness is ≤ 1 μm, which meets the processing requirements. Then, the aperture that meets the requirements is ultrasonically cleaned and dried.

[0057] Step 5: Use the nano-ion probe to test the loss of the aperture: install the tungsten aperture on the diaphragm plate D0 of the nano-ion probe instrument, adjust the physical position of the aperture and the primary beam focus position, and make the primary ion beam pass through the center of the aperture. Use the Beam Stability function in the Tunning software that comes with the nano-ion probe to record the change in the primary ion beam intensity, with a cumulative recording time of 24 hours and a recording interval of 5 minutes; compare the relative change rate of the primary ion beam intensity value at different time points with the initial value.

[0058] Example 2 The beam usage of the aperture is shown in the results (such as Figure 4 As shown in Table 1, the energy of the primary ion beam remains stable within 24 hours, indicating that the aperture ion primary beam current obtained by the preparation method of the present invention can remain stable for 24 hours. The existing aperture products with an aperture of 50 μm on the market, under the same conditions, the stability time of the beam current is only 0.7 hours (as shown in Table 1). Figure 5 As shown in the figure, the stable use time of the long-life aperture product prepared in Example 2 of the present invention is increased by about 36 times, achieving excellent technical effects.

[0059] In addition, the tested aperture was taken out from the nano-ion probe instrument and the aperture changes were observed using a stereo microscope, such as Figure 6 As shown, it is found that the aperture of the diaphragm has hardly changed before and after use, as well as in the aperture magnification diagram after use, which also reflects that the diaphragm loss of Example 2 is small, the stability is high, and the service life is longer.

[0060] Example 3

[0061] The processing and testing process is the same as that of Example 1, the only difference is that the temperature is raised at a uniform rate during the tempering process:

[0062] The fourth step is to temper the obtained aperture: the temperature is raised to 500°C at a constant speed of 5°C / min, kept at this temperature for 0.5 hours, and then naturally cooled to room temperature. All operations are carried out under nitrogen protection.

[0063] The results of the aperture stability test showed that the primary ion beam energy could remain stable for 28 hours (Table 1).

[0064] Comparative Example 1

[0065] The processing and testing process are the same as those of Example 2, the only difference being that step 4 is omitted and the aperture is not subjected to tempering treatment, that is, the aperture obtained in step 3 is inspected, cleaned, dried, and then subjected to loss testing.

[0066] The beam usage results are shown (such as Figure 7 As shown in the figure, the energy of the primary ion beam remained stable in the first 4 hours (with a change rate of less than 1%), but the beam current showed a downward trend after 4 hours; after 12 hours, the beam current decreased by 10%, indicating that the time for stable ion beam current energy was short.

[0067] In addition, the tested aperture was taken out from the nano-ion probe instrument and the aperture changes were observed using a stereo microscope (e.g. Figure 8 As shown in the figure, it was found that the aperture of the aperture increased significantly after use, which was contrary to the phenomenon of continuous decrease in beam current, indicating that slag was blocked in the small hole during the beam current test, indicating that the lack of low-temperature annealing treatment resulted in debris residue on the micropore wall, affecting the ion beam test.

[0068] It can be seen from the test data of Example 2 and Comparative Example 1 that the tempering treatment method of the present invention can effectively stabilize the stability of the metal near the aperture, thereby improving its strength, reducing the loss rate, effectively increasing the service life, and facilitating the detection and analysis process of the nano-ion probe.

Claims

1. A method for preparing a long-lived nano-ion probe aperture, characterized in that: The steps include: The first step is to prepare an aperture metal sheet; the aperture is made of tungsten; the thickness of the aperture metal sheet is 0.58-0.60 mm, the length is 20-30 mm, the width is 20-30 mm, and the roughness Ra is less than 0.1; In the second step, a conical pit structure is obtained on the surface of the aperture metal sheet by using an electric spark drilling method; In the third step, a micro-hole is machined in the center of the cone-shaped pit using a femtosecond laser, and the outer diameter of the aperture is cut using a wire to obtain the aperture; The fourth step is to temper the aperture; The tempering treatment is carried out in an inert atmosphere at a temperature of 450-500° C. for 1-2 hours and then naturally cooled to room temperature. The fifth step is to use a nano-ion probe to test the loss of the aperture.

2. The preparation method according to claim 1, characterized in that: In the second step, the depth of the conical pit structure is 0.45-0.60 mm and the cone angle is 85-95°.

3. The preparation method according to claim 1, characterized in that: In the second step, the conditions of the electric spark are as follows: peak current 8-12A, gap voltage 80-200V, pulse interval 1-100μs, and pulse width 1-100μs.

4. The preparation method according to claim 1, characterized in that: In the third step, the conditions of the femtosecond laser are: wavelength 1000~1100nm, power 5~20W, repetition rate 1Hz~1MHz, pulse width 190fs~10ps, and maximum pulse energy 10~100μJ.

5. The preparation method according to claim 1, characterized in that: In the third step, the diameter of the micropore is 50-100 μm, and the accuracy is ±5 μm; the aperture is a disc with an outer diameter of 1.98-2.02 mm.

6. The preparation method according to claim 1, characterized in that: The heating conditions during the tempering process are: When the temperature is lower than 200°C, the heating rate is 5~6°C / min; When the temperature is between 200℃~500℃, the heating rate is 1~2℃ / min.

7. The preparation method according to claim 6, characterized in that: The prepared aperture is installed into a nano-ion probe device to detect the energy change of the ion beam; The ion beam current energy change uses the Beam Stability function in the Tunning software to record the change of the primary ion beam current intensity, and calculate and compare the primary ion beam energy change rate.

8. Use of the aperture prepared by the preparation method according to any one of claims 1 to 7 in nano-ion probe detection and analysis.

Citation Information

Patent Citations

  • Method for clearing transmission electron microscope diaphragm by focused ion beam

    CN111266368A

  • Ultraviolet laser machining system of diaphragm for scanning electron microscope

    CN201154415Y